Trade in Global Value Chains : An Assessment of Labor Market Implications - Farole, Thomas; Hollweg, Claire; Winkler, Deborah (World Bank, Washington, DC, 2018)
The paper is structured in six further sections following this introduction. Section two develops a conceptual framework, and reviews the literature on the relationship between trade integration and labor market outcomes. Section three outlines the empirical framework and data used in the analysis. Section four presents results on the relationship between overall trade integration (through exports) and labor market outcomes. Section five then focuses specifically on GVC trade, and assesses the relationship between labor market outcomes and GVC integration as a buyer and as a seller. Section six tests if select policy indicators mediate these relationships between trade integration and labor market outcomes. Finally, section seven concludes, with a summary of results and areas for future research.